Brain-derived neurotrophic factor and stroke: perspectives on exercise as a health care strategy - De Assis, Gilmara Gomes [UNESP]; Murawska-Ciałowicz, Eugenia (Termedia Sp. z.o.o., 2024)
Purpose. Stroke is the second most common cause of mortality worldwide and the third most common cause of motor disability. From another perspective, brain-derived neurotrophic factor (BDNF) is a metabolite that plays several neuropro-tective roles. While cardiometabolic diseases are the leading cause of stroke, BDNF represents a target factor in the prevention and/or recovery from stroke. Aim: In this narrative review, we have summarised the clinical evidence of BDNF participation in the recovery from a stroke and discuss the potential use of exercise as a rehabilitation tool. Methods. Multiple combinations of the terms ‘brain infarction’, ‘cerebral infarction’, ‘hemorrhagic stroke’, ‘ischemic stroke’, ‘embolic stroke’ or ‘thrombotic stroke’ AND ‘BDNF’ or ‘pro-BDNF’ were used in PubMed databases. Studies not available in the English language or addressing animal experiments were excluded. Results and prospects. Seventeen clinical studies published up to June 30th of 2023 were included in this review. Changes in the patients circulating BDNF levels represent their capability of recovery from the stroke outcomes. A subtle, but consistent, negative inf luence of the presence of the 66Met-allele in BDNF on motor and cognitive competencies is seen in patients recovering from a stroke throughout the studies – an effect that is not reportedly detectable in other neuropatho-logical conditions. Exercise exerts a positive modulation on BDNF levels that accompanies improvements in stroke recovery and might exert a preventive role against the severity of stroke outcomes.
Keywords: BDNF; haemorrhagic stroke; ischemic stroke; metabolism; neuroplasticity